Pengaruh Keberadaan Direksi Perempuan dan Kepemilikan Institusional Terhadap Pengungkapan Kinerja Sosial - Sembiring, Etti Ernita; Kusumastuti, Endah Dwi (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to examine the effect of the presence of female directors, institutional ownership on social performance disclosure. The phenomenon of corporate social performance still occurs a lot. There are many cases of labor violations, which ultimately affect the company's reputation and shareholder value. Companies are required to disclose their social performance, whether the information is negative or positive. This study takes a sample of mining companies. The data are taken from annual reports and sustainability reports published in 2022 and 2023. The analysis used is panel data regression with the STATA analysis tool. This study also uses two control variables, namely company size and profitability (ROA). The results show that the presence of female directors, company size and ROA have a significant positive effect on social performance disclosure, while institutional ownership has no significant effect.